2020
DOI: 10.3390/su12030955
|View full text |Cite
|
Sign up to set email alerts
|

Green Awareness in Action—How Energy Conservation Action Forces on Environmental Knowledge, Values and Behaviour in Adolescents’ School Life

Abstract: Affordable, reliable, sustainable and modern energy consumption is a crucial goal of the Agenda 2030. To raise each citizen’s awareness for more effective energy consumptions, proper education is necessary. The classroom project GAIA (Green Awareness in Action) was designed to change energy consumption patterns to pursue green behaviour. The class-wise aim was to improve schools’ CO2-balance and to promote environmentally sustainable behaviour without impacting school life quality. Our target group were sixth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 57 publications
1
14
0
4
Order By: Relevance
“…Several studies have demonstrated that environmentally friendly lifestyles depend on three key factors: knowledge, values, and behavior [10][11][12]. More precisely, high environmental knowledge scores positively influence pro-environmental attitudes and behaviors [13,14]. Consequently, establishing in-depth sustainability knowledge will motivate learners to live a more sustainable lifestyle.…”
Section: Esd and Sustainabilitymentioning
confidence: 99%
“…Several studies have demonstrated that environmentally friendly lifestyles depend on three key factors: knowledge, values, and behavior [10][11][12]. More precisely, high environmental knowledge scores positively influence pro-environmental attitudes and behaviors [13,14]. Consequently, establishing in-depth sustainability knowledge will motivate learners to live a more sustainable lifestyle.…”
Section: Esd and Sustainabilitymentioning
confidence: 99%
“…This means that, in order to gain a broader knowledge of renewable energy sources, it is necessary to teach these topics from primary school to university [22]. The fact that related knowledge can be influenced by the education of the head of the household suggests that a more informed current generation can positively influence future generations, while this finding also proves the positive impact and importance of lifelong learning and adult education [39,40]. (5) Occupation and interest in the environment, in technology, or in engineering are positively related to knowledge about renewable energy sources, which is in line with the results of Karatepe et al (2012) [30].…”
Section: Awareness and Influencing Factors Related To Renewable Energmentioning
confidence: 99%
“…Green educational initiatives have shown that individual behaviour can be influenced positively in the course outreach modules, which has also been shown at the outreach facility Biosphere 2; there, students not only gained system knowledge based on an informal half-day educational program, the latter also induced changes in motivation or fascination, which affect behaviour accordingly [78]. Furthermore, a classroom project demonstrated that energy consumption can be reduced within a ten-week intervention based on a daily routine to prompt environmentally friendly behaviour [79]. In this case, students who demonstrate lower environmental behaviour scores increase their knowledge (action-related and effectiveness knowledge) to the same level as those with higher scores.…”
Section: Resultsmentioning
confidence: 93%